Dientamoeba fragilis in children: a systematic review on diagnostic considerations and efficacy of treatment. (2nd April 2020) - van Kalleveen, Michael W.; van Gool, Tom; Klarenbeek, Nikki; Benninga, Marc A.; Savelkoul, Paul H. M.; de Meij, Tim; Plötz, Frans B.
ABSTRACT: Introduction : The presence of D. fragilis in feces is characterized by an asymptomatic carrier ship to a spectrum of gastrointestinal symptoms. However, a causal relationship remains to be elucidated. In this systematic review, we aimed to evaluate the relationship between the eradication of D. fragilis and symptoms to establish the strength of evidence that D. fragilis in symptomatic children warrants antibiotic treatment. Areas covered : This systematic review covers a challenge in daily clinical practice. Is it necessary to test for D. fragilis in children with gastrointestinal symptoms and does a positive fecal PCR test warrant treatment? Expert opinion : Testing for D. fragilis seems justified in a selection of children with persistent unexplained chronic abdominal pain and diarrhea. Treatment of D. fragilis should be withhold until other causes like celiac disease have been excluded. Both microscopic and Real Time-PCR methods (or a combination of the two) can be used for diagnosis. Paromomycin or clioquinol are antibiotics of choice based on their small spectrum of activity, fewer side effects, and better eradication rates than metronidazole. Future randomized studies, with strict inclusion criteria, appropriate diagnostic testing, and doses of antibiotics based on bodyweight are warranted.